2023
DOI: 10.32920/14639502.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Challenges of Diabetes Self-Management in Adults Affected by Food Insecurity in a Large Urban Centre of Ontario, Canada

Abstract: Objective. To explore how food insecurity affects individuals’ ability to manage their diabetes, as narrated by participants living in a large, culturally diverse urban centre. Design. Qualitative study comprising of in-depth interviews, using a semistructured interview guide. Setting. Participants were recruited from the local community, three community health centres, and a community-based diabetes education centre servicing a low-income population in Toronto, Ontario, Canada. Participants. Twenty-one Englis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Diabetes self-care can be very complex, challenging and stressful [ 1 , 2 ], especially in developing countries where health care and formal support systems are still underdeveloped [ 3 ]. Daily self-management involves frequent blood glucose monitoring and insulin adjustments and administration, engaging in physical activities, consideration of nutrition, managing sleep duration and blood glucose level.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes self-care can be very complex, challenging and stressful [ 1 , 2 ], especially in developing countries where health care and formal support systems are still underdeveloped [ 3 ]. Daily self-management involves frequent blood glucose monitoring and insulin adjustments and administration, engaging in physical activities, consideration of nutrition, managing sleep duration and blood glucose level.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges can be at various levels, including the health system-level or individual-level, and the types of challenges vary in different parts of the world. [22][23][24][25] At the individual level, besides compliance with the medicines, a sustained self-care practice is required to achieve the therapeutic goals. 25 In India, individual self-care is often at stake due to a lack of fragmented information systems and inadequate patient support.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of support system related to family, peer group, friends, society, finance, professional assistance and medical guidance leads to negative impact on self-care behaviour. Although an important element, most the research evidences reported existence of poor support system (13,16,20). Not getting desired support from family members, lack of agreement on decisions making and conflict with the family members put a significant challenge (17).…”
Section: Lack Of Support Systemmentioning
confidence: 99%
“…Diabetes is a chronic ailment which needs lifelong adherence to many lifestyle modifications and treatment modalities. Degree and severity of symptoms have been found to be related with the practice of self-care care activities among diabetic persons (16,24). Moreover the presence of other comorbidities such as HTN, Hyperlipidaemia and obesity also impact significantly the self-management process.…”
Section: Severity Of Disease and Associated Co Morbiditiesmentioning
confidence: 99%
See 1 more Smart Citation